Practice of Organizational Development in a Domestic Company - Matkó, Andrea; Takács, B. (International Journal of Engineering and Management Sciences, 2018)
In today's changing world, it is extremely important that organizations can keep up with market trends. The perspectives of continuous development are expanding and the commitment of decision-makers to development activities is growing steadily. The starting point for organizational development is always man. Organizational development always begins with deeper research and modeling. Fundamental guidelines are set out as a paradigm of development. The most important and at the same time the most difficult step is to introduce the results of the analysis. The most effective, but the most time-consuming and cost-effective solution is full organizational development. The management of the organization faces significant efforts to embark on a full organizational development process. The aim of our study is to propose different development opportunities for the company's management with the help of analysis by the organization and supported by measurable data, as well as the catalyst for the modifying efforts observed among employees.